PENGARUH PROFITABILITAS,UKURAN PERUSAHAAN, PERTUMBUHAN ASET, DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL - INSIROH, LUSIA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract:The variables analyzed in this study are profitability, firm size, asset growth and asset structure Real estate and Property companies listed as sample, in which period the observations 2008-2012. The sample of this study is 23 companies. samples were taken by using purposive sampling method. multiple linear regression model by collecting data used in this study as a method of research analysis. The results showed that the structure of assets has a significant negative effect on the capital structure, while profitability, firm size, and growth of assets has no effect on the capital structure. Four independent variables simultaneously significant effect on the capital structure. The result of t-test shows that only structure of asset affect the capital structure significantly, while the result of F-test shows that the independent variabels affect five comma eight percentand ninety four comma two percent influenced by other factors not included in other research models. Keywords:capital structure, profitability, firm size, asset growth, and the structure of assets.